Spatial Distribution of Organic Pollution from Rubber Industry Effluent in the Ciseel River, Banjar City, Indonesia - Melly Mellyanawaty; Ira Sayanti (Faculty of Engineering, Universitas Serambi Mekkah, 2026)
Rubber-processing wastewater may contain organic matter, suspended solids, and nitrogen compounds that affect receiving rivers when treatment performance is unstable. This study evaluated treated rubber-industry effluent and the spatial distribution of pollutants in the Ciseel River, Batulawang, Banjar City, during dry and rainy conditions. River samples were collected at five points: 200 m upstream, the discharge mixing zone, and 300 m, 600 m, and 900 m downstream. The monitored parameters were TDS, EC, COD, TSS, total ammonia, total nitrogen, and pH. Effluent quality was compared with the Indonesian wastewater standard for rubber industries, while river water was assessed using Class IV criteria and the Pollution Index. COD and TSS exceeded the effluent limits in both seasons; COD reached 555.02 mg/L in the dry season and 455.31 mg/L in the rainy season. In the river, COD was the dominant parameter controlling water-quality status. Downstream COD remained above the Class IV criterion up to 900 m, showing that dilution and natural attenuation were insufficient within the monitored reach. The upstream stations met the standard, whereas the mixing zone and downstream stations were lightly polluted.